Implementation of Ethics Method (Ethics-Based Learning) in Islamic Education Learning at Islamic Private Vocational Schools, UISU Siantar Project - Muriati, Dewi Sri; Nasution, Alamsyah; Mayasari; Maisyarah, Rini; Siregar, Marlina (MANDAILING GLOBAL EDUKASIA, 2024)
Ethics and moral education plays an important role in shaping students' character, especially in facing increasingly complex social challenges. This study discusses the application of the Ethics-Based Learning method in developing the values ​​of honesty, patience, and caring in class X students of SMK Swasta Islam Proyek UISU Siantar. The main focus of this study is the material on avoiding free association and adultery as an effort to protect human dignity. The Ethics-Based Learning method is applied through an interactive learning approach, case discussions, moral reflection, and integration of religious and social values. The results of the study indicate that this method is effective in improving students' understanding and moral awareness, encouraging them to apply ethical principles in everyday life. Thus, the Ethics-Based Learning method can be a relevant strategy in character education, especially in forming a responsible attitude and upholding moral values ​​in social interactions.